2005
DOI: 10.1097/01.brs.0000152381.20719.50
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Laminectomy for Spinal Stenosis in Octogenarians

Abstract: On the long-term, decompressive laminectomy in selected octogenarians results in decreased disability, decline of analgesics usage, and increased quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 19 publications
4
44
1
4
Order By: Relevance
“…Previously, younger age has been found to be predictive of better postoperative walking ability in a 6 months' follow-up [15]. Generally, older age has not been found to predict poor clinical outcome in long-term studies [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, younger age has been found to be predictive of better postoperative walking ability in a 6 months' follow-up [15]. Generally, older age has not been found to predict poor clinical outcome in long-term studies [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…Cirak et al 6 concluded that in cases of lumbar spinal stenosis, decompressive laminectomy and extensive foraminotomy without instrumentation have good outcomes. Galiano and coworkers 10 showed that in the long term, decompressive laminectomies in selected octogenarians resulted in decreased disability, decline of analgesic use, and increased quality of life. However, there currently seems to be much less consensus regarding the extent of decompression in patients with lumbar spinal stenosis.…”
Section: Methods Of Decompression and Outcomementioning
confidence: 99%
“…27 There are also studies that present the opposite of these findings. 10,12 Some investigations undertaken for lumbar spinal stenosis surgery have noted that comorbidity is associated with poorer postoperative symptoms, motor function, and overall satisfaction. Katz et al 14 found that greater cardiovascular, musculoskeletal, and overall comorbidities led to poorer scores in most of the outcome measurements.…”
Section: Issues Associated With Elderly Patientsmentioning
confidence: 99%
“…Among patients 80 years and older undergoing laminectomy for spinal stenosis, Galiano et al 21 noted that at 2.7 years of follow-up, there was a 54.1% improvement in ODI and a statistically significant decrease in analgesic usage.…”
Section: Clinical Outcomementioning
confidence: 99%